Student's Progressive Perception And Learning Experience: Efficiency Of Self-Examination Simulation Platform In English Learning (ELT) - Ilfan Askul Pehala; Adzil Arsyi Sabana; Ahmad Ahmad (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. This article aims to analyze and describe students' progressivity in the English lecture. Progressivity is based on changes in perception variables and learning experiences based on the efficiency of using TOEFL AIO and CBT E-Learning. We followed descriptive qualitative design approach, using reflection sheet in questions to collect data who involved 77 students as participants through purposive sampling. Data was collected through the distribution of questions in reflection by using a combination of Open-ended and Close-ended Questions. The data were analyzed by coding to the variables and Spradley's ethnoscience analysis in describing the data by looking at the domain, taxonomy, and componential and expanding the interpretation by looking at the cultural themes of the existing data as main thematic analysis. The results show students believe that mental progressivity and student cognition that affect changes in student perceptions and learning experiences previously tended negative to progressive. Besides, they also believe the lecturers, as the main key role, determine whether there is progress or not and the application or platform will not play a role without the flexibility of the lecturer in the classroom. Then, the efficiency of the application and platform will impact students if the lecturer can make changes to student beliefs that have a domino effect on anxiety and internal motivation through a casual-contextual approach according to the perspective of the students themselves. As conclusion, this experience and progressivity were evaluated positively by them as long as ELT learning process activity puts students at the center and see how their perspectivesKeywords: Progressivity, Perception, Learning Experience, Platform And Application Efficiency